2007
DOI: 10.1590/s1413-86702007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and nutritional profile of individuals with chagas disease

Abstract: Epidemiological, clinical, nutritional, and biochemical data were collected, including gender, age, skin color, smoking, alcoholism, physical activity, weight, stature, body mass index, abdominal circumference, glycemia, and lipid profile. Fifty-three percent were male and 47% female; 96% were white skinned. Mean age was 49.6±6.36 years. The predominant form was indeterminate in 71%; smoking and drinking were recorded in 23% and 17%, respectively. Sedentariness predominated in 83%, and 55% presented increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
16
1
3
Order By: Relevance
“…Similarly, it has been reported that chagasic individuals residing in non-endemic areas of Brazil also manifested overweight [28], likely due to changes in their eating habits when migrating from endemic areas to large cities [29]. Within this setting, present patient series had increased insulin, triglycerides, HOMA-IR index in presence of lower levels of HDL likely compatible with a prediabetic situation, which in turn may increase the risk for cardiovascular disorders.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, it has been reported that chagasic individuals residing in non-endemic areas of Brazil also manifested overweight [28], likely due to changes in their eating habits when migrating from endemic areas to large cities [29]. Within this setting, present patient series had increased insulin, triglycerides, HOMA-IR index in presence of lower levels of HDL likely compatible with a prediabetic situation, which in turn may increase the risk for cardiovascular disorders.…”
Section: Discussionsupporting
confidence: 59%
“…Even if in recent studies [13] dysphagia appeared as a specific and constant symptom in patients with megaesophagus, in general the symptoms of chronic digestive CD are non-specific, and there are numerous confounders, including other common infections [14], [15], megacolon at high altitude, and gastrointestinal problems related to the long-term consumption of coca leaves [16]–[18] or to migration-related changes in diet [19], [20] and stress. A diagnosis of CD may easily be missed if symptoms are not evaluated by a physician who knew of the epidemiology and the symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…cruzi, em comparação aos não infectados 19 . Por outro lado, a análise dos dados de 66 pacientes adultos com sorologia positiva para doença de Chagas, atendidos no ambulató-rio da Faculdade de Medicina de uma universidade brasileira, demonstrou elevado percentual de obesidade (62%), avaliada pelo IMC, e de risco cardiovascular (55%), avaliado pelo elevado valor da CC 20 .…”
Section: Discussionunclassified